2016
DOI: 10.1016/j.rpped.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Circunferência da cintura como marcador para triagem de doença hepática gordurosa não alcoólica em adolescentes obesos

Abstract: The results presented here suggest that an increase in WC can reliably predict the risk of NAFLD in obese adolescents. This is a low cost and easy-to-use tool that can help in screening in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Recent epidemiological surveys have shown that the incidence of NAFLD in obese patients can reach 80%, and in severely obese patients who require bariatric surgery, the incidence of NAFLD is as high as 90% [4]. Independent associations between NAFLD and traditional obesity indicators BMI and WC have been demonstrated in many observational studies, but there is much debate as to which indicator is better at identifying obesity-related NAFLD risk [7][8][9][10][35][36][37][38][39]. Several recent studies have demonstrated that BMI was a stronger indicator of obesity for identifying and predicting NAFLD risk, with BMI having the largest AUC compared with other obesity-related parameters, showing better diagnostic performance than WC and other obesity indicators [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological surveys have shown that the incidence of NAFLD in obese patients can reach 80%, and in severely obese patients who require bariatric surgery, the incidence of NAFLD is as high as 90% [4]. Independent associations between NAFLD and traditional obesity indicators BMI and WC have been demonstrated in many observational studies, but there is much debate as to which indicator is better at identifying obesity-related NAFLD risk [7][8][9][10][35][36][37][38][39]. Several recent studies have demonstrated that BMI was a stronger indicator of obesity for identifying and predicting NAFLD risk, with BMI having the largest AUC compared with other obesity-related parameters, showing better diagnostic performance than WC and other obesity indicators [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com estudo realizado em sete países europeus, os resultados foram semelhantes, demonstrando que adolescentes europeus não cumprem as recomendações da AAP, (≥2h/dia), especialmente no final de semana 28 . Outra pesquisa apresentou prevalência geral de CS: 69,2% em dias de semana e 79,6% nos fins de semana 29 . O CS também tendo sido relacionado a reduções na expectativa de vida.…”
Section: Discussionunclassified
“…Previous studies have shown that increase in WC can reliably predict the risk of NAFLD in obese adolescents. [26]…”
Section: Discussionmentioning
confidence: 99%